(untitled) (Sirte University Journal of Humanities, 2024)
The study aimed to identify the impact of Organization Culture on Organizational Citizenship Behavior in The Libyan Academy in Benghazi. Descriptive approach has been used in the study. The questionnaire was developed based on some previous studies. The population of the study reached (171) employee, random sample selected was (120), with refund rate approximately of (82%). The results found that the overall level of Organization Culture and Organizational Citizenship Behavior were at a high degree. The results also indicated there was a significant effect of Organization Culture on Organizational Citizenship Behavior in The Libyan Academy, whereas there was a significant effect of the Organizational Norms and Organizational Values on Organizational Citizenship Behavior, but there wasn’t a significant effect of the Organizational Expectations and Organizational Beliefs on Organizational Citizenship Behavior in The Libyan Academy. Based on the results, the study came out with a set of recommendations that are expected to contribute to enhancing the effect Organization Culture on Organizational Citizenship Behavior in The Libyan Academy.